The exegetical encounter between Jews and Christians in late antiquity - Grypeou, Emmanouela.; Spurling, Helen. (Jewish and Christian Perspectives Series, 2009)
The 'Exegetical Encounter between Jews and Christians in Late Antiquity' is a collection of essays examining the relationship between Jewish and Christian biblical commentators. The contributions focus on analysis of interpretations of the book of Genesis, a text which has considerable importance in both Christian and Jewish tradition. The essays cover a wide range of Jewish and Christian literature, including primarily rabbinic and patristic sources, but also apocrypha, pseudepigrapha, Philo, Josephus and Gnostic texts. In bringing together the studies of a variety of eminent scholars on the topic of 'Exegetical Encounter', the book presents the latest research on the topic and illuminates a variety of original approaches to analysis of exegetical contacts between the two sets of religious groups. The volume is significant for the light it sheds on the history of relations between Jews and Christians in Late Antiquity.